KEARIFAN BUDAYA BALI MENGENAI TRADISI â€œNYAKAN DIWANGâ€ DALAM MEMBANGUN HARMONISASI UMAT BERAGAMA - Artiningsih, Ni Wayan Juli; Marselinawati, Putu Sri (Prodi Teologi Hindu STAH N Mpu Kuturan Singaraja, 2021)
This article will describe the existence of the Nyakan Diwang Tradition which is a religious activity that is dresta village (local wisdom), and is carried out from generation to generation by the people of Pakraman Munduk Village, Banjar District, Buleleng Regency. Indirectly, this tradition has become a medium for the people for dharmasanthi, forgiveness, and so on, as well as an expression of angayubagia (gratitude) in front of Ida Sang Hyang Widhi Wasa because on the support of His Waranugraha paper, Hindus in the village of Pakraman Munduk are always there. in a safe and healthy condition, so that we can together welcome the new Saka Year. Judging from the social aspect, the existence of this tradition has major implications in maintaining the stability of the social system, because in its implementation, interaction and communication between community members is absolutely necessary. This article will discuss (1) the process of implementing the Nyakan Diwang tradition (2) The function of the nyakan diwang tradition (3) The impact of the tradition on society and its preservation efforts. This article is the result of field research using ethnographic research methods that are descriptive qualitative.Â Keywords: Nyakan Diwang Tradition, Village Dresta, Social Community